LPI Air Defence Noise Radar - Molope, Lazarus Molahlegi (Department of Electrical Engineering, 2023)
This dissertation is for researching the feasibility of a Low Probability of Intercept (LPI), Air Defence (AD) Noise Radar with high range and doppler resolution. The research is approached by first simulating an S-Band LPI Noise Radar detecting a flying target and determining its range and velocity. The simulated Noise Radar is then implemented in the Universal Software Radio Peripheral (USRP) B210 H/W and tested against flying targets in monostatic mode. The actual results from H/W detection of real airborne targets are finally compared with simulated results.